Quantum Key Based Burst Confidentiality in Optical Burst Switched Networks - A. M. Balamurugan; A. Sivasubramanian (The Scientific World Journal)
The optical burst switching (OBS) is an emergent result to the technology concern that could achieve a feasible network in future. They are endowed with the ability to meet the bandwidth requirement of those applications that require intensive bandwidth. There are more domains opening up in the OBS that evidently shows their advantages and their capability to face the future network traffic. However, the concept of OBS is still far from perfection facing issues in case of security threat. The transfer of optical switching paradigm to optical burst switching faces serious downfall in the fields of burst aggregation, routing, authentication, dispute resolution, and quality of service (QoS). This paper deals with employing RC4 (stream cipher) to encrypt and decrypt bursts thereby ensuring the confidentiality of the burst. Although the use of AES algorithm has already been proposed for the same issue, by contrasting the two algorithms under the parameters of burst encryption and decryption time, end-to-end delay, it was found that RC4 provided better results. This paper looks to provide a better solution for the confidentiality of the burst in OBS networks.